Sentinel Node Biopsy in Young Patients with Atypical Melanocytic Tumors of the Head and Neck - David Pfau; Akina Tamaki MD; Kathryn R. Hoppe MD; Kord Honda MD; Rod Rezaee MD; Chad A. Zender MD (OTO Open, 2019)
Objective To examine the diagnostic value of the sentinel lymph node biopsy in pediatric through young adult head and neck melanocytic tumors of unknown malignant potential. Study Design Retrospective case series. Setting Single academic institution. Subjects and Methods Demographics, histology, and outcomes were examined in 14 patients aged 4 to 24 years with head and neck melanocytic tumors of unknown malignant potential. Information on age at diagnosis, primary lesion characteristics, and sentinel lymph node biopsy were compared. Results Of 14 patients meeting criteria for head and neck melanocytic tumors of unknown malignant potential, 8 patients underwent sentinel lymph node biopsy (57%). Of those, 4 biopsies (50%) had positive sentinel nodes. All patients undergoing sentinel lymph node biopsy had primary lesions greater than 1 mm depth or mitotic rate of at least 1 mitosis per mm 2 . No patients had recurrence of their primary lesion at time of follow-up. Conclusion Our data show a high rate of node-positive sentinel lymph node biopsy for pediatric and young adult head and neck patients with melanocytic tumors of unknown malignant potential, supporting the value of sentinel lymph node biopsy in this population.